Biventricular pacemaker therapy improves exercise capacity in patients with non‐obstructive hypertrophic cardiomyopathy via augmented diastolic filling on exercise. (23rd January 2020) - Ahmed, Ibrar; Loudon, Brodie L.; Abozguia, Khalid; Cameron, Donnie; Shivu, Ganesh N.; Phan, Thanh T.; Maher, Abdul; Stegemann, Berthold; Chow, Anthony; Marshall, Howard; Nightingale, Peter; Leyva, Francisco; et al.
Abstract : Aims: Treatment options for patients with non‐obstructive hypertrophic cardiomyopathy (HCM) are limited. We sought to determine whether biventricular (BiV) pacing improves exercise capacity in HCM patients, and whether this is via augmented diastolic filling. Methods and results: Thirty‐one patients with symptomatic non‐obstructive HCM were enrolled. Following device implantation, patients underwent detailed assessment of exercise diastolic filling using radionuclide ventriculography in BiV and sham pacing modes. Patients then entered an 8‐month crossover study of BiV and sham pacing in random order, to assess the effect on exercise capacity [peak oxygen consumption (VO2 )]. Patients were grouped on pre‐specified analysis according to whether left ventricular end‐diastolic volume increased (+LVEDV) or was unchanged/decreased (–LVEDV) with exercise at baseline. Twenty‐nine patients (20 male, mean age 55 years) completed the study. There were 14 +LVEDV patients and 15 –LVEDV patients. Baseline peak VO2 was lower in –LVEDV patients vs. +LVEDV patients (16.2 ± 0.9 vs. 19.9 ± 1.1 mL/kg/min, P = 0.04). BiV pacing significantly increased exercise ΔLVEDV ( P = 0.004) and Δstroke volume ( P = 0.008) in –LVEDV patients, but not in +LVEDV patients. Left ventricular ejection fraction and end‐systolic elastance did not increase with BiV pacing in either group. This translated into significantly greater improvements in exercise capacity (peak VO2 + 1.4 mL/kg/min, P = 0.03) and quality of life scores ( P = 0.02) in –LVEDV patients during the crossover study. There was no effect on left ventricular mechanical dyssynchrony in either group. Conclusion: Symptomatic patients with non‐obstructive HCM may benefit from BiV pacing via augmentation of diastolic filling on exercise rather than contractile improvement. This may be due to relief of diastolic ventricular interaction. Clinical Trial Registration: ClinicalTrials.gov NCT00504647.